Characteristics of the Psychrotrophic Molds Obtained from Indigenous Fermented Dairy Products Samples - Basavabharati; N. Suchithra; R. Prabha (Research Perspectives of Microbiology and Biotechnology Vol. 5, 2024)
Aims: Indigenous fermented milk products like mishtidoi, shrikhand, lassi and buttermilk that are famous products of West Bengal, Maharashtra, Punjab, and Karnataka, respectively. Nowadays, they are available all over India and are liked by the majority of the human population. These are fermented products acidic in nature, contain sugar that favours the growth of molds and thus require refrigeration to increase the shelf life. Prolonged storage of these products may provide good growth conditions for psychrotrophic molds which grow at lower temperatures. This may lead to the deterioration of products by the proteinases and lipases produced by molds and few of the psychrotrophic molds excrete mycotoxins making the product unsafe for consumption. With this background, the present study was taken up to find the types of psychrotrophic molds in Indigenous fermented milk products available in the Bengaluru market as well as to characterize their nature. Study Design: In order to study the types of psychrotrophic molds present in indigenous fermented milk products, unbranded (n=6) and branded (n=15) samples such as mishtidoi, shrikhand, lassi and buttermilk were collected from Bangalore markets and subjected to isolation of molds at low temperature (0-70C) using selective medium and further the isolates obtained were identified based on their characteristics. Place and Duration of Study: The research work was conducted in the Department of Dairy Microbiology, Dairy Science College, Karnataka Veterinary, Animal and Fisheries Sciences University (KVAFSU), Hebbal, Bengaluru, 560 024, Karnataka, India between June 2014 to June 2015 as part of postgraduate research work, Hebbal, Bangalore-24 and literature was updated recently. Methodology: The market samples of indigenous fermented dairy product samples were subjected to pour plating using sterile malt extract agar adjusted to pH 3.5 and incubated plates at 5oC for 25 days. The mold isolates obtained were identified by colony morphology, microscopic examination for cell morphology and specific biochemical tests. Results: A total of 21 psychrotrophic mold isolates were obtained from branded and unbranded indigenous fermented milk products. Among 21 psychrotrophic molds, 6 and 15 isolates were obtained from unbranded and branded samples, respectively. Based on the preliminary identification, the isolates were characterized as Penicillium spp., (n=3), Mucor spp., (n=2) and Cladosporium spp., (n=1) from unbranded samples while branded indigenous fermented dairy product samples showed Penicillium spp., (n=9) and Alternaria spp., (n=6) were isolated from branded samples. According to pheno and genotypic characterization, the isolates were identified as Penicillium chrysogenum (57.12%), Alternaria alternata (28.56%), Mucor mehei (9.52%) and Cladosporium cladosporioides (4.76%) at the species level. Except for unbranded mishitdoi, all types of indigenous fermented dairy product samples were found to contain psychrotrophic molds. Conclusion: Penicillium chrysogenum was the most abundant species found especially in branded butter milk indicating longer refrigeration may lead to the selection of psychrotrophic molds due to low-temperature storage and favourable pH (3-5) of the indigenous fermented dairy product samples. This psychrotrophic mold produced citrinin, a mycotoxin that affects the liver. Hence care must be taken to avoid consumption of long-stored refrigerated indigenous fermented products like lassi and buttermilk.